(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Sultan Hasanuddin 02 Training Ship which is a place for learning theory and practice of students at the Makassar Maritime Polytechnic. So that in supporting its operations requires periodic maintenance management that will ensure smooth and optimal performance in all supporting aspects. Likewise in the implementation of regulations that have required all ships to operate to install an Oil Water Separator that can separate oil and water before being dumped / falling into the sea. The use of Oil Water Separator must be maximized so that it can work properly, so it is necessary to carry out periodic and regular maintenance, the importance of maintenance management aims to evaluate the performance and effectiveness of the Oil Water Separator (OWS) in managing oil waste on ships by improving and increasing effectiveness and productivity in the utilization process to support smooth ship operations. Before making preparations in the maintenance stage, it is better to first make a proper plan and in accordance with the guidelines and also pay attention to field conditions both in terms of human resources and supporting spare parts and appropriate equipment. This study aims to evaluate the performance and effectiveness of the Oil Water Separator (OWS) in managing oil waste on the Sultan Hasanuddin training ship. By looking at the ship’s ability to manage oil waste properly which will provide a positive image for the ship’s Officers and Crew who are responsible for the environment, support sustainable practices and can increase trust from regulators and customers. Based on the results of field observations, there is still effectiveness in OWS performance with routine maintenance showing better separation efficiency than those that are rarely checked. However, the level of cleanliness of the effluent of the maintained OWS ranges from 5-10 ppm, while the unmaintained OWS reaches 20-50 ppm. The availability of spare parts and the level of personnel training are significant challenges.